Service Learning Project: Conflict Resolution in the Playground - Esteban Vega, Sandra; García Asenjo, Ángel; Ternero Cuesta, Candela (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2021)
This Service-learning project aims to work on conflict resolution with 4th and 5th Primary schoolers during recess hours while in the playground and the school canteen. The aim of this paper is twofold: 1-address some of the most common issues in Primary Education, like bullying, and 2-explain what Service learning (Sl) is all about. this project's purpose is to develop and promote students' social skills based on the different proposed dynamics in order to improve their self-concept and self-esteem. In order to develop the social abilities that allow mediation in the different conflicts, a set of activities will be developed, thus fulfilling this project's objectives. the project presented here aims to be applicable to any educational centre altogether with a subsequent assessment.
Keywords: Service-learning; Primary Education; students; coexistence; conflict resolution; activities; communication; participation